Joining of 3D-printed AlSi10Mg by friction stir welding - Du, Zhenglin (2020)
Friction stir welding is a solid-state welding technology capable of joining metal parts without melting. The microstructure of the material evolved during the process from columnar grain along the thermal gradient in the melt pool to fine equiaxed grains. A significant decrease in microhardness in the stir zone was observed with the lowest hardness at approximately 3 mm from the weld centre. The decrease in the microhardness is mainly attributed to the dissolution of hardening precipitates in the aluminium matrix. Defects in the weld were observed due to insufficient heat input. Heat input could be increased with the increase in rotational speed of the welding tool, with some improvements in strength.